Relaciones interpersonales en el comercial Ayatolla del cantón las Naves - Chávez Mendoza, Daniela Nayeli (2022)
This paper focuses on the study of interpersonal relationships in the workplace, considering the case of Commercial Ayatolla in the canton of Las Naves, Bolivar province, with the purpose of analyzing interpersonal relationships in Comercial Ayatolla. To successfully complete the development of this study, the explanatory method was used, conducting a survey of the staff, where it is concluded that in the business there are different negative situations among employees, such as poor communication, discussions, demotivation, among others, making the business does not offer a quality service, due to internal inconsistencies and customers prefer to shop elsewhere, Therefore, it is possible to recommend that Comercial Ayatolla could improve productivity by promoting teamwork, effective internal communication and defining institutional values, so that human relations in the store are optimal, so that work is coordinated, and employees perform their tasks more efficiently and effectively.